Downregulation of hepatitis C virus replication by miR‐196a using lentiviral vectors. (10th March 2021) - Shafaati, Maryam; Jamalidoust, Marzieh; Kargar, Mohammad; Arefian, Ehsan; Kafilzadeh, Farshid
Abstract: Hepatitis C virus (HCV) is a positive‐sense, single‐stranded RNA virus that causes chronic hepatitis and hepatocellular carcinoma. Cellular microRNAs (miRNAs) directly modulate the viral infectivity and indirectly through targeting virus‐related host factors. They play an essential role in the progression of different stages of HCV infection. The roles of miR‐196 family in HCV infection and hepatocellular carcinoma progression remain poorly understood. Using ViTa databases, miR‐196a as a high‐score miRNA targeting the NS5 A region of HCV genome was selected. Using dual luciferase assay and an established cell‐cultured HCV (HCVcc) system, the effect of miR‐196a on HCV genome was assessed. In silico analysis demonstrated the significant role of miR‐196a in the downregulation of HCV replication. Using dual luciferase assay, the liver‐specific miR‐196a and NS 5 A gene binding was confirmed. To assess the experimental role of miR‐196a, an HCVcc system was established in the Huh 7.5 cell lines. The HCV‐RNA 1b derived from an infected patient was transfected into Huh 7.5 cells containing miR‐196a lentiviral vectors (Huh 7.5/miR‐196a), mocks (Huh 7.5/mock vector), and naïve Huh 7.5 cells. The rate of reduction of the HCV genome replication was assessed using relative real‐time PCR assay. These results represent miR‐196a overexpression and its roles in regulating HCV genome replication. However, miR‐196a may inhibit HCV replication and accelerate the early stages of apoptosis. Overexpression of miR‐196a in Huh 7.5 replicon cell is a potential new strategy to prevent hepatitis C infection. The results of this study suggest that miR‐196a directly downregulates HCV replication and may serve as a new antiviral therapy.